Integrating Sustainability into Microfinance Marketing: A Comprehensive Framework - Madya, Aldi Ihsan (Indonesian Scientific Publication, 2025)
Microfinance institutions (MFIs) play a highly strategic role in empowering micro, small, and medium enterprises (MSMEs) and promoting inclusive economic growth in developing countries. With increasing global emphasis on sustainability, MFIs are now expected to integrate environmental and social responsibility into their core marketing strategies alongside economic goals. However, existing studies often address green marketing, social responsibility, and digital inclusion separately, resulting in fragmented insights. This study seeks to fill that gap by developing an integrated conceptual model for sustainability-oriented microfinance marketing. Employing a Systematic Literature Review (SLR) guided by the PRISMA protocol, this study systematically analyzes 56 peer-reviewed articles published between 2018 and 2024 using thematic synthesis and bibliometric mapping. The findings reveal that combining green marketing, socially responsible marketing, and digital inclusion enables MFIs to enhance brand differentiation, client trust, and outreach while aligning with global sustainability agendas. The proposed model offers both theoretical contributions and practical relevance for MFIs aiming to create long-term social, environmental, and financial impact. Challenges such as limited digital and environmental literacy, resource constraints, and infrastructural barriers are acknowledged, with strategic responses including education, partnerships, and incentive-based solutions. This study lays a foundation for future empirical research and policymaking to support the transformation of MFIs into agents of sustainable development.